ENGAGING STUDENTS WITH SOME LEARNING PLATFORMS: ENGLISH TEACHERS' PERCEPTION - Lasmi Febrianingrum; Wahab Syakhirul Alim (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to describe the perception of English teachers about the use of platforms in engaging students during online learning. The participants of this study consist of junior and senior high school teachers in some schools in Madura. Their perceptions were investigated in terms of three aspects: effects of using this learning platform on their perceived motivation, the perceived usefulness, and the perceived ease of use of platforms. The study was conducted in the descriptive method. The data were collected by using a questionnaire and self-structured online interviews. The findings indicated that the teachers perceived that google classroom as the most used LMS and WhatsApp as the most preferred social media since both are user friendly and easy to use. Furthermore, Microsoft PowerPoint or Word and YouTube are the most preferred platform since they are motivating, useful and engaging during English online learning. It was found out that the English teachers are satisfied with the features of the use of these outstanding platforms in their online learning since they provide suitable features for their materials. Moreover, it was found that some teachers choose those platforms since they are more familiar for them to use. Besides, they had been introduced, acquired knowledge and practices on how to use the platform for supporting the learning process. Consequently, it should be training for the teacher about other outstanding learning platforms to be acknowledged and employed in their teaching and learning process.